PENGEMBANGAN JARINGAN DISTRIBUSI AIR BERSIH KECAMATAN PELING TENGAH - Sampe, Nober; Tunas, I Gede; Andiese, Vera Wim (Jurusan Teknik Sipil Universitas Tadulako, 2013)
This study aims to provide an overview of the development planning of water distribution networks in the village of Patutuki District of Peling Tengah, considering the region located in the coastal areas with limited of surface water sources, moreover the constriction and leakage in pipelines and water quality containing calcium or poor maintenance, so the flow of water to the consumer is reduced. The scope of study is limited to the analysis of the availability of water discharge mainstay as one of the water sources in the village Patutuki using FJ. Mock and calculate the domestic water supply in the village of Patukuki District of Peling Tengah depended on the number of population. Furthermore, network planning distribution of domestic water in the service area by gravity through the branching system and closed pipes. For secondary data collection was carried out in the form of meteorological data, population data, topographic data and the data of land-use. Then calculate the water needs to be compared with the discharge mainstay. The result is the minimum river discharge mainstay of Bebek River which is the main water source to meet water needs in the area of service to 20 years .The maximum pressure meets the maximum permissible limit of 10 kg/cm2 and also meet the maximum speed limit is a maximum of 3 m3/sec. For the required number of plumbing needs in this plan that HDPE pipe ø 102 mm by 108 rods , PVC pipe ø 102 mm 33 rods , PVC pipe ø 76 mm 557 rods , and PVC pipe ø 51 mm 749 rods. Keywords: water distribution networks, domestic water, Peling Tengah